Resources for the Teaching of Aging to Undergraduates: An Annotated Bibliography - Haq, Haris (Journal of English Language Teaching and Applied Linguistics, 2021)
There is no doubt that ageism is an important topic of study in academic circles as we aim to build more inclusive and equitable environments to facilitate tertiary learning. In the succeeding annotated bibliography, a list of resources that can offer ideas on the topic of teaching of ageism to undergraduates is put forward. These resources include content on why ageism is important as a topic, its importance in the university classroom, and practical applications related to its instruction. To achieve this, this annotated bibliography draws from evidence in research related to gerontology, educational psychology, and social justice pedagogy, amongst other areas. It is hoped that this paper can serve as a guide to academics interested in educating and empowering their students to become more aware of this major form of discrimination.